Sustainable intensification of oilseed brassica based production systems under semi-arid climates: Sustainable intensification of oilseed brassica based production systems under semi-arid climates - R S JAT; R L CHOUDHARY; H V SINGH; P K RAI (Journal of Oilseeds Research, 2023)
Technologies to decrease non-renewable energy use in agriculture production may recuperate the energy balance and C emission in the atmosphere. Conservation Agriculture (CA) practices are getting pace world-wide to answer declining factor productivity, deteriorating soil health, climate change, farm profitability and sustainability. Permanent beds with residue retention (PB+R) improved mustard seed yield (15.4%), system grain yield (10.6%), consumed less C input (-17%) and C foot prints (-25%), and recorded more C output (12%), C net (21%), C efficiency (47%) and C sustainability (47%) compared to conventional tillage without residues (CT-R). Diversification of traditional fallow-mustard (F-M) system with maize-mustard rotation (Mz-M) increased system grain yield (142.9%), sustainable yield index (376.5%), production efficiency (177.2%), economic efficiency (94%) and irrigation water productivity (66%) compared with F-M under CT-R.